Distribution of calbindin-D28k in endocrine cells of the gastrointestinal tract and pancreas and of some endocrine glands (thyroid, parathyroid, pituitary, adrenals) in rats - Timurkaan, S.; Tarakci, B. G. (Ecole Nationale Veterinaire Toulouse, 2007)
Distribution of calbindin D28k in the thyroid, parathyroid, pituitary, adrenals, pancreas, small and large intestines, and in stomach from 6 adult Wistar rats were investigated immunohistochemically using an antiserum raised against the 28kD calbindin from chicken duodenum. Parathyroid, intestine and pancreatic endocrine cells failed to react with the antibodies whereas immunoreactivity was markedly found in the thyroid parafollicular cells, in the epithelial cells of the adenohypophysis, in the adrenal chromaffin cells and also in nerve fibres from neurohypophysis and adrenal medulla. Calbindin immunoreactivity was rare in stomach. All the tested animals presented the same profile of calbindin D-28k localisation. The presence of calbindin D28k in the epithelial cells and in the nerve fibres suggest that this calcium binding protein is probably involved in the regulation of the intracellular Ca2+ pool.
Keywords: immunohistochemistry; calbindin-D28k; thyroid; hypophysis; adrenal medulla; rat